2002
DOI: 10.1080/073993302753429022
|View full text |Cite
|
Sign up to set email alerts
|

Information Women Receive About Heart Attacks and How It Affects Their Knowledge, Beliefs, and Intentions to Act in a Cardiac Emergency

Abstract: In this study we investigate (a) what information women receive on acute myocardial infarction (AMI) from different information sources, (b) how women evaluate this information, and (c) how information acquisition is related to women's knowledge of AMI, personal risk perceptions, and behavioral intentions regarding a cardiac emergency. A random sample of 844 women 50 years and over were telephoned in the state of Washington. Repeated measures regression analyses showed that women receive most of their informat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
22
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 21 publications
5
22
0
Order By: Relevance
“…In this study, we found a positive association between CVD knowledge and risk perception among participants. This is consistent with other study findings (Choi et al, 2008;Homko et al, 2008;Jones et al, 2007;Meischke et al, 2002). Therefore, lack of CVD knowledge may contribute to low level of risk perception.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In this study, we found a positive association between CVD knowledge and risk perception among participants. This is consistent with other study findings (Choi et al, 2008;Homko et al, 2008;Jones et al, 2007;Meischke et al, 2002). Therefore, lack of CVD knowledge may contribute to low level of risk perception.…”
Section: Discussionsupporting
confidence: 93%
“…Perceived health status was found to be strongly associated with CVD risk perception, as has been shown in previous studies (Frijling et al, 2004;Meischke et al, 2002). These results suggest that blue-collar workers who report their health status to be good feel less vulnerable to having any diseases, including CVD.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…A 1997 national poll commissioned by the National Health Council and Robert Starch Worldwide entitled 'Americans Talk about Science and Medical News' [as cited in (Johnson, 1998)] showed that the respondents' primary sources of medical news were television (40%), doctors (35%), magazines or journals (35%) and newspapers (16%). Studies by Johnson and Meischke (Johnson and Meischke, 1992a,b) clearly identified media as a main source of cancer-related information and a study by Meischke et al (Meischke et al, 2002) showed that women reported mass media as the most frequently reported source of information on heart attacks, followed by health care providers.…”
Section: Introductionmentioning
confidence: 99%